MORAL VALUES DILEMMAS IN BULGARIAN EDUCATION (Global Journal of Advanced Engineering Technologies and Sciences, 2015)
Main focus of the article is the transformation of values in a situation of ideological and their subsequent collapse. Problematize is value vacuum in which younger generations grow up and lack of supports for the formation of moral literacy. To overcome the problem of threshold seek opportunities to introduce value orientations by finding compatibility between civic education and non-confessional religious education. Outlines projections for: - implementation of practical value model called: democratic citizenship and ethical.